2014
DOI: 10.1186/1471-2458-14-207
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, blood pressure, and glucose and lipid metabolism among permanent and fixed-term workers in the manufacturing industry: a cross-sectional study

Abstract: BackgroundTemporary employment, a precarious form of employment, is recognized as social determinant of poor health. However, evidence supporting precarious employment as a risk factor for health is mainly obtained from subjective data. Studies using objective clinical measurement data in the assessment of health status are limited. This study compared body mass index (BMI), lipid and glucose metabolism, and health-related lifestyle factors between permanent workers and fixed-term workers employed in the manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Most of the educational sessions covered lifestyle modification, focusing on improving diet, increasing physical activity, and smoking cessation. Three studies had environmental level interventions that involved providing a Japanese style healthy lunch 64) in one case and a Mediterranean lunch 54) in another and environmental prompts 48) in the form of brief messages that encourage employees to make healthy choices such as low calorie foods at vending machines and increase physical activity at staircases. Only one study 58) reported using a behavioral change model as a basis for planning the intervention but did not specify the model.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the educational sessions covered lifestyle modification, focusing on improving diet, increasing physical activity, and smoking cessation. Three studies had environmental level interventions that involved providing a Japanese style healthy lunch 64) in one case and a Mediterranean lunch 54) in another and environmental prompts 48) in the form of brief messages that encourage employees to make healthy choices such as low calorie foods at vending machines and increase physical activity at staircases. Only one study 58) reported using a behavioral change model as a basis for planning the intervention but did not specify the model.…”
Section: Resultsmentioning
confidence: 99%
“…Psychological stress and physical health problems in non-standard workers increase the risk of chronic and acute diseases; furthermore, the social, physiological, and self-rated health of workers become lowered [ 30 ]. Finally, the difference in socioeconomic status due to unstable employment is a factor for health deterioration and social determinants of health [ 1 ]. Problems associated with low socioeconomic status among these non-standard workers have a greater impact on female workers than male workers, which ultimately increases the prevalence of MetS among female non-standard workers.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 2008 financial crisis, economic uncertainty has persisted throughout the world and this has resulted in continual job instability [ 1 ]. In Korea, unstable jobs such as non-standard employment began to emerge during the International Monetary Fund (IMF) economic crisis in 1997, and this trend has continued to this day [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistencies have emerged, for example, between studies that report worse health outcomes ( e.g. Benavides, Duran & Gimeno, 2015 ; Inoue, Minami & Yano, 2014 ; Kim, Khang & Muntaner, 2008 ; Minelli, Pigini & Chiavarini, 2014 ; Pirani and Salvini, 2015 ; Quesnel-Vallée, DeHaney & Ciampi, 2010 ; Waenerlund et al, 2011 ) and those that report similar or better outcomes among temporary workers ( e.g. Bardasi & Francesconi, 2004 ; De Moortel, Vandenheede & Vanroelen, 2014 ; Liukkonen, Virtanen & Kivimäki, 2004 ; Virtanen, Vahtera & Kivimäki, 2002 ).…”
Section: The Social and Health Consequences Of Temporary Employmentmentioning
confidence: 99%